Variations in the interaction of human defensins with Escherichia coli: Possible implications in bacterial killing - Mathew, Basil; Nagaraj, Ramakrishnan (PLOS ONE, 2017)
Human α and β-defensins are cationic antimicrobial peptides characterized by three disulfide bonds with a triple stranded β-sheet motif. It is presumed that interaction with the bacterial cell surface and membrane permeabilization by defensins is an important step in the killing process. In this study, we have compared interactions of three human α-defensins HNP3, HNP4, HD5 and human β-defensins HBD1-4 that are active against Escherichia coli, with its cell surface and inner membrane as well as negatively charged model membranes. We have also included the inactive α-defensin HD6 in the study. Among the α-defensins, HNP4, HD5 and HD6 were more effective in increasing the zeta potential as compared to HNP3. Among the β-defensins, HBD1 was the least effective in increasing the zeta potential. The zeta potential modulation data indicate variations in the surface charge neutralizing ability of α- and β-defensins. Comparison of E. coli inner membrane and model membrane permeabilizing abilities indicated that HD5, HD6 and HBD1 do not permeabilize membranes. Although HBD4 does not permeabilize model membranes, considerable damage to the inner membrane of E. coli is observed. Our data indicate that mammalian defensins do not kill E. coli by a simple mechanism involving membrane permeabilization though their antibacterial potencies are very similar.